Frequency of déjà rêvé: effects of age, gender, dream recall, and personality - Schredl, Michael; Funkhouser-Flueckiger, Arthur Taylor; Göritz, Anja (Journal of consciousness studies, 2017)
Déjà rêvé (‘already dreamed’) has been hypothesized as a cause for various forms of déjà experience. With déjà rêvé one has the distinct impression that the uncanny familiarity one is sensing has come from a preceding dream, but one not usually remembered until the experience is taking place. In this exploratory investigation, 2,492 respondents filled out online questionnaires in which they were queried about the incidence of their déjà rêvé experiences, about dream frequency, and about their attitudes to dreams. The Big Five personality factors were also measured using a separate, standardized questionnaire. Nearly 80% claimed to have had such experiences and the associated frequencies are presented. Age was negatively correlated with the incidence and there was little gender dependence. The results of the Big Five personality factors are also presented. Suggestions are made for future research.
Gesehen am 21.08.2018